The Effect of Service Quality and Facilities on Loyalty Through Satisfaction in Mekaar Syariah Financing in Buton Area PT. Permodalan Nasional Madani - Pramuji, Gema Arief; Agus Salim (Dinasti Publisher, 2023)
The aims of this study was to analyze the effect of service quality and facilities on loyalty through satisfaction with financing Mekaar Syariah Area Buton PT. Permodalan Nasional Madani. The research method is a quantitative method with survey techniques, involving distributing questionnaires through an online platform to collect data from a sample of 168 respondents. The statistical test used in this study is the SmartPLS-based Structural Equation Modeling (SEM) analysis. The results showed that there was an effect of service quality and facilities on loyalty through customer satisfaction and customer satisfaction could mediate the effect of service quality and facilities on loyalty. The better the quality of services and facilities, the higher the customer loyalty.